2017
DOI: 10.12659/msm.902752
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Neutrophil-to-Lymphocyte Ratio in Locally Advanced Rectal Cancer Treated with Neoadjuvant Chemoradiotherapy

Abstract: BackgroundIncreasing evidence suggests that cancer-associated inflammation is associated with poorer outcomes. The neutrophil-to-lymphocyte ratio (NLR), considered as a systemic inflammation marker, is thought to predict prognoses in colorectal cancer. In this study, we explored the association between the NLR and prognoses following neoadjuvant chemoradiotherapy (CRT) for locally advanced rectal cancer (LARC).Material/MethodsFrom February 2002 to December 2012, a group of 202 patients diagnosed with LARC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
2
23
2
Order By: Relevance
“…Jinwen Shen et al [17] defined the cutoff value of NLR in their study to be 2.7 ± 1.5 and they found that it didn't correlate with any clinico-pathologic characteristics except age; furthermore it didn't correlate with any survival outcomes, our results didn't come into alignment with that of Jinwen Shen possibly as this study dealt with those patients with locally advanced cancer rectum only who were decided to be treated with neoadjuvant CRT.…”
Section: Discussionmentioning
confidence: 59%
“…Jinwen Shen et al [17] defined the cutoff value of NLR in their study to be 2.7 ± 1.5 and they found that it didn't correlate with any clinico-pathologic characteristics except age; furthermore it didn't correlate with any survival outcomes, our results didn't come into alignment with that of Jinwen Shen possibly as this study dealt with those patients with locally advanced cancer rectum only who were decided to be treated with neoadjuvant CRT.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have evaluated the prognostic and predictive value of neutrophil-to-lymphocyte ratio (NLR) in peripheral blood of cancer patients. NLR is commonly used as a measure of systemic inflammation, and it has been shown to predict patient clinical outcome in a number of human cancers, such as rectal (Shen et al 2017), esophageal (Nakamura et al 2017), prostate (Gokce et al 2016), pancreatic (Kadokura et al 2016), and breast cancer (Ethier et al 2017). Overall, a high NLR score was associated with worse survival and retained a more consistent prognostic value among patients with an advanced disease stage, who are also more likely to receive chemotherapy treatments or who are not operable (Guthrie et al 2013).…”
Section: Tams and Tans As Prognostic/ Predictive Biomarkers In Cancermentioning
confidence: 99%
“…Several studies have evaluated the prognostic and predictive value of neutrophil‐to‐lymphocyte ratio (NLR) in peripheral blood of cancer patients. NLR is considered an indicator of systemic inflammation and predicted patient clinical outcome in several human cancers, such as rectal, esophageal, prostate, pancreatic, and breast cancer . Moreover, a high NLR score was associated with worst survival and displayed a more consistent prognostic value among patients with advanced disease .…”
Section: Introductionmentioning
confidence: 99%